Personal Emergency Notification Application for Mobile Devices (International Journal of Engineering and Computer Science, 2015)
In most recent years, many interesting applications for mobile devices are designed to improve our living quality and deal with house care issues under Android framework. In this paper, an emergency notification application for mobile devices will be designed. In the application, the position function of GPS and an easy used interface capable for sending emergency notification messages or recording systems are included. The application implements a location awareness system which gives the user’s current location, sends this location using SMS (Short Message Service) plus sharing location with friends and family and save the voice recording for future reference. Users can take benefit of this application in emergency situations by using emergency feature of this application. To get the location coordinates, application is using GPS (Global Positioning System) as location provider. The application design has five parts: a mobile client, a application server, a database, GPS system and a map service. A mobile client which consists of a mobile and GPS receiver finds the location of the user to get aware of his location. In order to share this location the mobile client sends this location to the application server from where other users can get this location if they have the authentication provided by the user. Personal emergency notification system is an important tool for personal security and safety.